2011
DOI: 10.1111/j.1465-3435.2011.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Dialogic Research to Overcome Poverty: from principles to action

Abstract: In the EU commitment to alleviating the high rates of poverty in Europe there is widespread agreement among policy‐makers that it is crucial to include the voices of those who are living in poverty in order to fight exclusion most effectively. Similarly, those studying ways to address poverty and inequality are increasingly required to seek dialogue with those who are the focus of their research. These policy‐makers and researchers need procedures that will allow them to move from the principle of including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 20 publications
0
13
0
4
Order By: Relevance
“…These actions are characterised by reorganising the available resources in the school and the community to support all pupils' academic achievement, instead of segregating some of them according to ability or by lowering down their educational opportunities. SEAs derive from a rigorous analysis of the educational systems, theories and practices, particularly, from the successful actions identified in 27 case studies across the European Union of schools serving families from low socioeconomic status where children achieve excellent results (Valls & Padrós, 2011). For instance, some SEAs studied through the INCLUD-ED Project are interactive groups, dialogic reading, after-school clubs and some family education programmes like the dialogic literary gatherings.…”
mentioning
confidence: 99%
“…These actions are characterised by reorganising the available resources in the school and the community to support all pupils' academic achievement, instead of segregating some of them according to ability or by lowering down their educational opportunities. SEAs derive from a rigorous analysis of the educational systems, theories and practices, particularly, from the successful actions identified in 27 case studies across the European Union of schools serving families from low socioeconomic status where children achieve excellent results (Valls & Padrós, 2011). For instance, some SEAs studied through the INCLUD-ED Project are interactive groups, dialogic reading, after-school clubs and some family education programmes like the dialogic literary gatherings.…”
mentioning
confidence: 99%
“…SEAs improve educational outcomes for many children and adolescents (Flecha and Soler, 2013). These actions are derived from a rigorous analysis of educational systems, especially 27 case studies in schools attended by families of low socioeconomic status who still obtained excellent educational outcomes in schools throughout Europe (Valls and Padros, 2011).…”
Section: Family Education In Learning Communitiesmentioning
confidence: 99%
“…Specifically, McLoyd (1998) showed that living in extreme poverty persistently has particularly negative effects. In this sense, poverty alleviation is one of the five priority themes of the Europe 2020 strategy adopted by the European Council (European Commission, 2010a) that commits EU actors and Member States to work for smart, sustainable and integrated growth (Valls and Padros, 2011). Education and permanent education became a key strategy in European policies guaranteeing immigrants' social and economic integration (De Paola and Brunello, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…En este sentido, diversos autores han identificado aquellos elementos que sí conducen al éxito de las intervenciones como por ejemplo elaborar políticas y acciones contra la pobreza basadas en evidencias científicas (Ríos, 2013) y contar con las voces de las personas implicadas en las problemáticas sociales (Valls & Padrós, 2011).…”
Section: Marco Teóricounclassified